Using Benchmarking Techniques and the 2011 Maternity Practices Infant Nutrition and Care (mPINC) Survey to Improve Performance among Peer Groups across the United States - Edwards, Roger A. (J Hum Lact, 2014)
BACKGROUND: A substantial proportion of US maternity care facilities engage in practices that are not evidence-based and that interfere with breastfeeding. The CDC Survey of Maternity Practices in Infant Nutrition and Care (mPINC) showed significant variation in maternity practices among US states. OBJECTIVE: The purpose of this article is to use benchmarking techniques to identify states within relevant peer groups that were top performers on mPINC survey indicators related to breastfeeding support. METHODS: We used 11 indicators of breastfeeding-related maternity care from the 2011 mPINC survey and benchmarking techniques to organize and compare hospital-based maternity practices across the 50 states and Washington, DC. We created peer categories for benchmarking first by region (grouping states by West, Midwest, South, and Northeast) and then by size (grouping states by the number of maternity facilities and dividing each region into approximately equal halves based on the number of facilities). RESULTS: Thirty-four states had scores high enough to serve as benchmarks, and 32 states had scores low enough to reflect the lowest score gap from the benchmark on at least 1 indicator. No state served as the benchmark on more than 5 indicators and no state was furthest from the benchmark on more than 7 indicators. The small peer group benchmarks in the South, West, and Midwest were better than the large peer group benchmarks on 91%, 82%, and 36% of the indicators, respectively. In the West large, the Midwest large, the Midwest small, and the South large peer groups, 4–6 benchmarks showed that less than 50% of hospitals have ideal practice in all states. CONCLUSION: The evaluation presents benchmarks for peer group state comparisons that provide potential and feasible targets for improvement.